Residential radon in Galicia: a cross-sectional study in a radon-prone area. (28th July 2017) - Lorenzo-González, María; Ruano-Ravina, Alberto; Peón, Joaquín; Piñeiro, María; Barros-Dios, Juan Miguel
Abstract: Residential radon exposure is a major public health problem. It is the second greatest cause of lung cancer, after smoking, and the greatest in never-smokers. This study shows the indoor radon exposure distribution in Galicia and estimates the percentage of dwellings exceeding reference levels. It is based on 3245 residential radon measurements obtained from the Galician Radon Map project and from controls of two previous case-control studies on residential radon and lung cancer. Results show a high median residential radon concentration in Galicia (99 Bq m −3 ), with 49.3% of dwellings having a radon concentration above 100 Bq m −3 and 11.1% having a concentration above 300 Bq m −3 . Ourense and Pontevedra, located in South Galicia, are the provinces with the highest median indoor radon concentrations (137 Bq m −3 and 123.5 Bq m −3, respectively). Results also show lower radon levels in progressively higher building storeys. These high residential radon concentrations confirm Galicia as a radon-prone area. A policy on radon should be developed and implemented in Galicia to minimize the residential radon exposure of the population.